Primary embryonic cells of Rhipicephalus microplus and Amblyomma cajennense ticks as a substrate for the development of Borrelia burgdorferi (strain G39/40) - Rezende,J. (2012)
Borrelia burgdorferi, the agent of Lyme borreliosis, is a spirochetes transmitted by ticks to humans and animals. Its cultivation in vitro in tick cells allows studies of its biology and provides methodology for future research in Brazil, and for the isolation of Borrelia spp. We examined in vitro the characteristics of embryonic cells of Rhipicephalus microplus and Amblyomma cajennense in cell culture and investigated the suitability of embryonic cells as a substrate for cultivation of B. burgdorferi. Subcultures were prepared from primary cultures of embrionary cells of R. microplus and A. cajennense maintained in Leibovitz's (L-15) complete medium at 28 ºC and 31 ºC, respectively. When a monolayer had formed, the L-15 was replaced with Barbour-Stoener-Kelly medium for experiments to infect cell cultures with B. burgdorferi. After 72 hours of cultivation, the spirochetes were counted using an inverted phase contrast microscope and dark-field illumination (400×). Survival, multiplication and the adherence of B. burgdorferi for embryonic cells of R. microplus and A. cajennense were observed. B. burgdorferi cultured with embryonic cells of R. microplus grew on average to a density (final count) of 2.4 × 10(7) spirochetes/mL, whereas in cell-free culture, an average of 2.5 × 10(7) spirochetes/mL were counted. When cultivated with A. cajennense cells, the final count of spirochetes was on average 1.7 × 10(7) spirochetes/mL, while spirochetes cultured under cell-free conditions replicated on average of 2.2 × 10(7) spirochetes/mL. Similar results were observed in the final count of Spirochetes cultivated in cells of R. microplus and A. cajennense, when compared with cell-free control. These results demonstrated that cells of R. microplus and A. cajennense have the potential to be used as growth substrate for B. burgdorferi in the study of its interaction with host cells.